Pengaruh Inflasi, Nilai Tukar dan GDP Malaysia Terhadap Ekspor Komoditas Lemak dan Minyak Hewan/Nabati Provinsi Riau Ke Malaysia - Atila Ramadhanilla; Anthony Mayes; Ando Fahda Aulia (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Riau Province is one of the five largest contributing provinces to Indonesia’s exports, with Malaysia serving as the primary destination country within ASEAN. Animal and vegetable fats and oils constitute the largest commodity exported to Malaysia. This study aims to examine the influence of inflation, the exchange rate, and Malaysia’s GDP on Riau Province’s exports of animal and vegetable fats and oils to Malaysia during the quarterly period of 2010–2024. The data used are secondary time-series data, and the analytical method employed is multiple linear regression using the Ordinary Least Squares (OLS) technique, with EViews 12 as a statistical analysis tool. The independent variables in this study include Riau Province’s inflation, the Rupiah–US Dollar exchange rate, and Malaysia’s GDP, while the dependent variable is Riau Province’s exports of animal and vegetable fats and oils to Malaysia. The partial results show that inflation has a positive and insignificant effect on these exports. The Rupiah–US Dollar exchange rate has a negative and significant effect, while Malaysia’s GDP has a positive and significant effect on Riau Province’s exports of animal and vegetable fats and oils to Malaysia. Simultaneously, the findings indicate that all independent variables collectively influence these exports